KEEFEKTIFAN MODEL PROBLEM POSING PADA PEMBELAJARAN MENULIS TEKS RESENSI CERPEN DI KELAS XI SMAN 1 CIKALONGWETAN - Resti Mustika; Dian Septiani; Diena San Fauziya (IKIP Siliwangi, 2019)
Regarding the implementation of the current 2013 curriculum, students are required to play an active role in learning various kinds of texts, especially short story review texts. This study aims to find out (1) differences pretest and posttest using the problem posing model on learning to write short story review texts in class XI A2 SMAN 1 Cikalongwetan; (2) differences in aspects of the elements / systematics and language rules in the short story review text pretest and posttest using the problem posing model on learning to write short story review texts in class XI A2 SMAN 1 Cikalongwetan; (3) the effectiveness of the problem posing model in learning to write short story review texts in class XI A2 SMAN 1 Cikalongwetan. The method used in this research is pre experimental design with form (one group pretest-posttest). The sample taken was 28 students. The results showed an average initial test score of 46.25 and an average final test score of 78.57 which meant that posttest was better than prettest. There are significant differences in aspects of the content details and elements / systematics of short story review texts. Based on the results of the paired sample t-test, the Sig (2-tailed) value was 0,000 <0,05. Thus, the problem posing model is effective in learning to write short story review texts.